2008
DOI: 10.1002/bjs.6072
|View full text |Cite
|
Sign up to set email alerts
|

Female sexual dysfunction after ileal pouch–anal anastomosis

Abstract: Almost half of the respondents reported having sexual dysfunction. Although poor pouch function was not identified as an important predictor of sexual dysfunction in this series, larger studies may be required to identify associated prognostic factors clearly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 22 publications
4
37
1
5
Order By: Relevance
“…Therefore the International Index for Erectile Function [IIEF] for males and the Female Sexual Function Index [FSFI] for femaleswere used in the majority of the studies. 7,8,11,13,14,15,16,17,19,20 The majority of the studies examined sexual function in both males and females and thus the results are not presented based on sex. Instead the results are presented based on participant selection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore the International Index for Erectile Function [IIEF] for males and the Female Sexual Function Index [FSFI] for femaleswere used in the majority of the studies. 7,8,11,13,14,15,16,17,19,20 The majority of the studies examined sexual function in both males and females and thus the results are not presented based on sex. Instead the results are presented based on participant selection.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies showed an impaired sexual function among IBD patients, with female patients more adversely affected compared with males. 9,12,13,14 Furthermore, depression was identified as the most consistent negative predictive factor of sexual function across studies, which could be attributed to the chronic course of the disease. 9,10,11,14 It has been reported that the relationship between chronic conditions and depression or anxiety can be experienced as independent or inter-related [with either one causing the other].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Both instruments have been used in previous studies on patients with IPAA. 13,14,19,20 Hormonal replacement therapy (HRT) for women and injection or oral therapy for erectile dysfunction for men were also recorded. 27,28 Body image was assessed using a 10-item scale, the Body Image Scale (BIS), consisting of affective items (e.g.…”
Section: Sexual Functionmentioning
confidence: 99%
“…impotence, impaired lubrication, pain during intercourse and desire, vary. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] This aspect of quality of life is poorly considered in standard instruments. Reported improvement of sexual function may be an effect of excision of the source of chronic inflammation and a better general health status.…”
Section: Introductionmentioning
confidence: 99%